Pengaruh Lingkungan Bisnis Dan Strategi Operasional Terhadap Kinerja Operasional Pada Outlet Fast Food Di Kabupaten Bekasi - Candra Dwi Hardiana; Ikhlas Ridho’i (Jurnal Ekonomi dan Bisnis, 2022)
The business environment and operational strategy have an important role for a company, namely as the influence of all activities or activities in achieving the goals of a company. Therefore, companies are required to be able to optimize their operational performance. This study aims to determine whether the business environment and operational strategies partially and simultaneously affect operational performance.The research method used is by distributing questionnaires given to 35 managers and assistant managers in each outlet as respondents to obtain information and to collect data by asking each respondent to answer each statement listed on the questionnaire given.Based on the results of this study partially variable X1 and X2 plays an important role for the variable Y. however it has no positive effect on Y, because x1 has a Sig. obtained is 0.500 > 0.05 and the t value is - 0.682 < 1.3433, and X2 has a Sig. obtained 0.356 > 0.05 and the t value is -0.937 < 1.3433. So it can be concluded that H1 and H2 are rejected. Based on the results of this study simultaneously the variables of the business environment and operational strategy with the Sig. 0.539 > 0.05, which means that it is greater than α = 0.05 and the analysis of the F test results is 0.631. So it is concluded that the business environment and operational strategy do not have a significant effect on operational performance simultaneously. This result implies that the business environment (X1) and operational strategy (X2) in explaining or influencing operational performance (Y) at fast food outlets in Bekasi District are 3,8% while 96,2% is explained by other factors outside the business environment and operational strategy, such as work environment, employee morale, innovation strategy, motivation, work discipline, HR management strategies, and supply chain.